Patient safety culture among nursing professionals in a philanthropic hospital in Minas Gerais - Magalhães, Eduarda Vieira; de Paiva, Fernanda Oliveira; Alves, Maria Eduarda Soares; de Almeida, Meire Cavalieri (Revista Cuidarte, 2021)
Introduction: Different initiatives have been carried out with a view to improving the quality of patient care and safety in Brazil. However, compliance with these standards as a number of requirements does not seem to correspond to the actual incorporation of changes and improvement in security. Objectives: Evaluate the patient’s safety culture in a philanthropic hospital in Minas Gerais, also possible differences between work, day and night shiftes Methods: This is an observational cross-sectional study. The study population consisted of nursing professionals working in this philanthropic institution. For the evaluation of the safety culture, the Hospital Survey on Patient Safety Culture (HSOPSC), created by the Agency for Healthcare Research and Quality (AHRQ), validated, translated and adapted transculturally in Brazil was used. In the analysis and interpretation of the data, the guidelines of the AHRQ were followed, and strengthened and fragile dimensions were observed. This work was approved by the Research Ethics Committee. Results: We included 118 participants in the study, 17.2% of these total nurses and the rest of the nursing technicians. No dimension of the security culture has been identified as strengthened in the institution. Fragile areas were considered: "communication openness", the "teamwork within units", the "staffing", the "handoffs and transitions", and the "nonpunitive response to error". In some dimensions, differences were observed by work shift, day and night. Conclusion: The analysis of the safety culture in this hospital can contribute to a better direction of conduct so as to ensure safer care. How to cite this article: Magalhães, Eduarda Vieira; de Paiva, Fernanda Oliveira; Alves, Maria Eduarda Soares; de Almeida, Meire Cavalieri. Cultura de segurança do paciente entre profissionais de Enfermagem em um hospital filantrópico de Minas Gerais. Revista Cuidarte. 2021;12(3): e1990. http://dx.doi.org/10.15649/cuidarte.1990